Musical Analysis of Chanting Melodies in the Teochew Chinese Yoga Tantra Ritual in Thailand - Sornchai, Rachan; Pidokrajt, Narongchai; Amatyakul, Poonpit (Journal of Urban Culture Research, 2025)
This study explores the musical elements of the Dharma Sankhita chants in the Mahayana Teochew Chinese Yoga Tantra ritual at Kak Hang Niam Huk Lim Monastery, Bangkok, Thailand. It examines the ritual’s background and musical analysis. Practiced by both Teochew and Cantonese Chinese, the ritual known in Teochew as “Bang Iem Kao” is a profound act of filial piety and ancestor veneration, rooted in the Eight Cardinal Virtues of Chinese ethics. The ceremony is held to dedicate merit to deceased ancestors and preserve cultural traditions. It can be performed at both family and community levels, encouraging intergenerational participation and solidarity. The ritual typically takes place during the seventh lunar month and includes mournful, intense chanting in harmony with the meanings of sacred mantras. The chants are categorized into four rhythmic groups: Jang, Jiu, Gi, and Bung, each with distinct tempos. This musical tradition reflects the deep spiritual beliefs and rich cultural heritage of the Teochew Chinese community.